Comparative Study of Crucial Properties of Packaging Based on Polylactide and Selected Essential Oils - Ewa Olewnik-Kruszkowska; Astha Vishwakarma; Magdalena Wrona; Anis Bertella; Anna Rudawska; Magdalena Gierszewska; Beata Schmidt (Foods)
In order to establish the differences in packaging containing various essential oils, polylactide (PLA)-based polymeric films incorporating poly(ethylene glycol) (PEG), clove (C), grapefruit (G), rosemary (R), and tea tree (T) essential oils were obtained and subsequently analyzed. In addition to examining structure and morphology, the polymer films underwent analyses that are particularly important with regard to contact with food. Mechanical and antioxidant properties, water vapor transmission rate (WVTR), and analysis of barrier properties against ultraviolet (UV) radiation, as well as the migration of ingredients into food simulants such as 10% v/v solutions of ethanol, 3% w/v acetic acid solution, and isooctane, were among the critical studies conducted. A comparison of the properties of the obtained materials allowed us to establish that the incorporation of essential oils significantly increases elongation at break and enhances UV barrier properties. In the case of materials containing clove oil and tea tree oil, a reduction in WVTR of about 1 g/m2/h was observed. The migration of the ingredients present in the films filled with clove oil, grapefruit oil, and tea tree oil into the acetic acid solution did not exceed 10 mg/kg, which is an acceptable value according to the European Union restrictions. Taking into account all of the studied properties, it should be stressed that the most promising packaging material is the film filled with clove oil.